Refugees and Knowledge Production Europe's Past and Present - Kmak, Magdalena; Björklund, Heta (Studies in Migration and Diaspora, 2022)
Building on research within the fields of exile studies and critical migration studies and drawing links between historical and contemporary 'refugee scholarship', this volume challenges the bias of methodological nationalism and Eurocentrism in discussing the multifaceted forms of knowledge emerging in the context of migration and mobility. With critical attention to the meaning, production and scope of 'refugee scholarship' generated at the institutions of higher education, it also focuses on 'refugee knowledge' produced outside academia, and scrutinizes the conditions according to which it is validated or silenced. Presenting studies of historical refuge and exile, together with the experiences of contemporary refugee scholars, this book will appeal to scholars across the social sciences with interests in forced migration, refugee studies, the sociology of knowledge and the phenomenon of 'insider' knowledge, and research methods and methodology.